TANTANGAN BERBAHASA: ANALISIS KESALAHAN BAHASA PADA PROPOSAL PKM MAHASISWA TEKNIK UNIVERSITAS NEGERI MEDAN - Rozi, Soraya; Kustiawan, Wanda Nur Akila; Syahri, Salwa Khairi Alfi; Aprilliany, Fenny; Chairunnisa, Hera (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
This study analyzes the language errors found in the Student Creativity Program (PKM) Proposal compiled by Engineering students of the State University of Medan (UNIMED). The errors analyzed include aspects of spelling, sentence structure, and the use of words with the affix "di". Data were collected through document analysis methods with a qualitative descriptive approach. The results of the study indicate that students still have difficulty in constructing effective sentences that are in accordance with good Indonesian language rules. Factors causing errors include students' lack of understanding of language norms and minimal guidance in this aspect. This study recommends increasing guidance related to scientific writing and organizing workshops to improve the quality of PKM proposals in the future. Thus, it is hoped that the resulting proposals will be more competitive at the national level.